A novel patient‐oriented numerical procedure for glaucoma drainage devices. (19th September 2018) - Mauro, Alessandro; Massarotti, Nicola; Mohamed, Salahudeen; Uña, Ignacio Rodríguez; Romano, Mario R.; Romano, Vito
Abstract: The present work analyses the performance of four glaucoma drainage devices, by means of a novel patient‐oriented numerical procedure. The procedure is based on the three‐dimensional geometry reconstruction from the stacks of tomographic images of a human eye, at different angles, on meshing and on thermo‐fluid dynamics modelling activities, carried out on the reconstructed computational domain. The current three‐dimensional eye model considers anterior chamber (AC), trabecular meshwork, Schlemm's canal, and collector channels, making use of generalised porous medium approach for modelling ocular porous tissue and cavities. The intraocular pressure (IOP) management inside AC of human eye is analysed, by comparing the results obtained for four drainage devices implanted in a human eye for glaucoma treatment, ie, ExPRESS shunt, iStent inject, SOLX gold micro shunt, and the novel silicon shunt device. The numerical results allow predicting the effects of the installation of these implants on human eyes, in terms of IOP decrease, aqueous humour velocity, pressure, friction coefficient, and local Nusselt number, pointing out the clear distinction between pre‐operative and post‐operative eye conditions for different glaucoma surgical techniques. Abstract : A novel 3D numerical procedure has been developed to reproduce the operation of Glaucoma Drainage Devices (GDDs) surgically implanted in subject specific human eyes. The present procedure allows to predict the post‐operative conditions of the patient, such as Intraocular Pressure (IOP) and Aqueous Humor (AH) flow resistance. The surgical choice of a specific GDD for glaucoma surgery could take into account the post‐operative data calculated by using the proposed numerical approach, to be considered as a valuable support to surgeons.